2023
DOI: 10.18632/aging.204811
|View full text |Cite
|
Sign up to set email alerts
|

Expression, prognostic value and mechanism of SP100 family in pancreatic adenocarcinoma

Abstract: Background: Pancreatic adenocarcinoma (PAAD) is one of the most aggressive malignancies with a very poor prognosis. Exploring more therapeutic targets and prognostic biomarkers is of great significance to improve the prognosis of PAAD patients. Increasing evidence supports that the speckled protein (SP) 100 family is associated with human cancer and immune disorders. However, the function of the SP100 family members in PAAD is still unclear. Methods: R, Cytoscape, cBioPortal, and other software and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Altered expression or mutations in these proteins can influence gene regulation and potentially contribute to tumor development (Seeler et al., 1998 ; Yordy et al., 2004 ). A previous study demonstrated a significant association between high SP family member expression in pancreatic adenocarcinoma (PAAD) and unfavorable clinicopathological characteristics as well as a poor prognosis for patients with PAAD (Duan et al., 2023 ). SP110 and SP140 showed high rates of nonsynonymous mutations in head and neck squamous cell carcinoma (Chang et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Altered expression or mutations in these proteins can influence gene regulation and potentially contribute to tumor development (Seeler et al., 1998 ; Yordy et al., 2004 ). A previous study demonstrated a significant association between high SP family member expression in pancreatic adenocarcinoma (PAAD) and unfavorable clinicopathological characteristics as well as a poor prognosis for patients with PAAD (Duan et al., 2023 ). SP110 and SP140 showed high rates of nonsynonymous mutations in head and neck squamous cell carcinoma (Chang et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Gene families are established through a shared ancestral origin and demonstrate significant structural and functional resemblances, leading to the generation of related protein products [ 1 ]. Numerous gene families have been confirmed to be associated with the process of carcinogenesis [ 2 , 3 ]. The tripartite motif (TRIM) family has more than 80 members and is primarily distinguished by the interesting new gene (RING) domain, which serves as an E3-ubiquitin ligase [ 4 ].…”
Section: Introductionmentioning
confidence: 99%